Application Of Tailing Sand And Water As Backfill Material In Metal Mines (1992) - Sun Henghu (International Conference on Ground Control in Mining, 1992)
This paper analyses problems associated with cement based technique in metal mines, and provides a new mining technique of packing the tailing sand and water into solidified material. In the new technique, the cementing agent is a solidifying material containing a high percentage of water and tailing sand. The sand and water solidify into the packed body at the same time. The slurry of the packed body varies widely in concentration and suitability for different mining conditions. It consists of two liquid materials, each composed of a cementing agent, tailing sand and water. The thick liquids are transported to the packing place at the same time. Their pumping property is good; they do not solidify or block up the pipe during transportation. At the packing place, the two liquids are evenly mixed. The mixed liquid flattens out well and its solidifying speed is so fast that it solidifies into a packed body within a very short period of time. The compressed strength of the packed body can reach 1.2-5MPa in one day, which satisfies the requirements of different mining conditions. By using the new mining technique, all the tailing sand can be used again in the packed body and it is low in cost and investment. The mechanisation is easy and thus the working efficiency is increased and the use of labour decreased. Contamination problems caused by excess water drainage under the ground are resolved.